Laser plasma interaction physics on the LIL facility - Masson-Laborde P.-E.; Depierreux S.; Michel D.T.; Hüller S.; Pesme D.; Robiche J.; Loiseau P.; Tikhonchuk V.T.; Stenz C.; Nicolaï P.; Casanova M.; Teychenne D.; et al. (EPJ Web of Conferences, 2013)
We present an overview of the interpretation of laser plasma interaction (LPI) experiments carried out on the LIL facility. These multikilojoule experiments have been done using underdense foam targets at 0.351 μm laser light leading to high temperature and large plasmas. We discuss the interpretation using our different numerical tools: hydrodynamics simulations carried out with the code FCI2 to characterize the plasma, linear gain estimates with the postprocessor Piranah and paraxial simulations with the code HERA.